Pengaruh Kepemimpinan Terhadap Inovasi dalam Organisasi Kewirausahaan - Ari Wibowo Sembiring; Aulia Sari Damanik; Khansa Arista Widya; Suawandi Suawandi (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This research aims to investigate the impact of leadership on innovation in the context of entrepreneurial organizations. Effective leadership has been proven to be a key factor in driving innovation, a key element for entrepreneurial sustainability and growth. To explain the relationship between leadership and innovation, this study uses a comprehensive research approach, including document analysis, surveys, and interviews. Findings suggest that leadership that inspires, supports, and models innovation can have a significant impact on an organization's entrepreneurial ability to create and implement innovation. These findings provide valuable insights for practitioners and policy makers in the context of entrepreneurial organizations and demonstrate the important role for leaders in developing a strong innovation culture. In an era of constant change, innovation has become a key factor for the survival of entrepreneurial organizations, and effective leadership can play an important role in encouraging and driving the innovation process. This study provides an in-depth analysis of a number of leadership variables, including leadership style, decision-making skills, and communication, and how these variables impact an organization's ability to create, adopt, and implement innovation. It also emphasizes the important role of leaders in creating a culture of innovation that supports and encourages creativity throughout entrepreneurial organizations. The implications of this research are important for leaders and policymakers seeking to optimize the role of leadership in supporting the long-term success of innovative and entrepreneurial organizations.